L'art en Belgique. Flandre et Wallonie au xx siècle un point de vue. - PARIS MUSEES (Paris : Musées, 1990)
van den Berghe, Frits ; Broodthaers, Marcel ; Charlier, Jacques ; Colinet, Paul ; de Cordier, Thierry ; Delvaux, Paul ; Dujourie, Lili ; Ensor, James ; Geys, Jef ; Joostens, Paul ; Khnopff, Fernand ; Magritte, René ; Mariën, Marcel ; Mesens, E.L.T. ; Nougé, Paul ; Panamarenko ; Permeke, Constant ; Rops, Félicien ; Servranckx, Victor ; Spilliaert, Léon ; Vantongerloo, Georges ; Vercruysse, Jan ; Wéry, Marthe ; Wiertz, Antoine
boek